2019
DOI: 10.1104/pp.19.00336
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA166 Monitors SPOROCYTELESS/NOZZLE for Building of the Anther Internal Boundary

Abstract: The internal boundary between inner and outer microsporangia within anthers is essential for male fertility of vascular plants. Dehiscence zones embedded in the boundary release pollen for fertilization. However, the molecular mechanism underlying boundary formation in anthers remains poorly understood. Here, we report that microRNA166 (miR166) and its target PHABULOSA (PHB) regulate SPOROCYTELESS/NOZZLE (SPL/NZZ), which controls microsporogenesis. In developing anthers of Arabidopsis (Arabidopsis thaliana), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…AtPHB and AtFIL , which are the homologues of CiPHB1 and CiFIL , were used as marker genes. As the expression patterns of these two genes have been reported before ( Siegfried et al 1999 ; Li et al 2019 ), only some typical data is shown here. In the young stamen of arabidopsis, when the four-microsporangia pattern was established, AtPHB expression in the anther was restricted in the stomium regions between the inner and outer microsporangia ( Fig.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…AtPHB and AtFIL , which are the homologues of CiPHB1 and CiFIL , were used as marker genes. As the expression patterns of these two genes have been reported before ( Siegfried et al 1999 ; Li et al 2019 ), only some typical data is shown here. In the young stamen of arabidopsis, when the four-microsporangia pattern was established, AtPHB expression in the anther was restricted in the stomium regions between the inner and outer microsporangia ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…In contrast to flat organs such as leaves, the stamen development process undergoes substantial morphological changes. Correspondingly, the expression patterns of adaxial–abaxial polarity marker genes also change dynamically in this process ( Sessions et al 1997 ; Toriba et al 2010 ; Li et al 2019 ). In the spherical stamen primordium of rice, the adaxial marker gene is initially expressed in the domain adjacent to the meristem, and the abaxial marker is expressed on the opposite side, as in the primordia of other lateral organs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The miR166 family has 13 members in the rice genome, forming six mature isoforms ( Table 1). The function of miR166 has been reported in plant development, targeting transcription factor genes of the class III homeodomain-leucine zipper family, such as PHABU-LOSA and PHABOLUTA, to specify the fate of the shoot apical meristem (Zhu et al 2011;Li et al 2019b). Its function in plant immunity has been reported only in rice.…”
Section: The Micrornas That Play Positive Roles In Rice Immunity Agaimentioning
confidence: 99%